Analisis Dimensi Sosial Ekonomi Rumah Tangga Petani Cengkeh Di Desa Lipulalongo Kecamatan Labobo Kabupaten Banggai Laut Provinsi Sulawesi Tengah - Aprianto, Moh. Yayan Rizky; Azuz, Faidah; Sheyoputri, Aylee Christine Alamsyah (PALLANGGA: Journal of Agriculture Science and Research, 2024)
Discussing clove farmers is inseparable from the socio-economic dimensions of farmers, this can be used as a benchmark to see social status, production and income to be used as material for the development of farmer quality. The aim of this research is to determine the socio-economic dimensions of clove farmer households. This research was conducted in Lipulalongo Village, Labobo District, Banggai Laut Regency, Central Sulawesi Province from June to July 2023. Respondents in this study were clove farmers with a total of 43 farmers. The analysis used is descriptive qualitative analysis by explaining in depth matters relating to the socio-economic clove farmers. The results of this study are: on the social dimension, the age of the farmer is in the productive period, the education of clove farmers is in the tertiary education level, the ownership of productive trees is 25-199 trees, and the position of clove farmers in society is ordinary society with several farmers including in traditional figures, religious figures, and government figures. The economic dimension is in the form of farmers' income from clove production where the income of clove farmers is at a value of Rp. 1,000,000 – Rp. 20,000,000 per season harvest. Membahas tentang petani cengkeh tidak terlepas kaitannya dengan dimensi sosial ekonomi petani. Hal ini dapat dijadikan tolak ukur untuk melihat status sosial, hasil produksi, dan juga pendapatannya untuk dijadikan bahan guna perkembangan kualitas petani. Tujuan Penelitian ini mengetahui dimensi sosial ekonomi rumah tangga petani cengkeh. Penelitian ini dilaksanakan di Desa Lipulalongo, Kecamatan Labobo, Kabupaten Banggai Laut, Provinsi Sulawesi Tengah pada bulan Juni – Juli 2023. Responden dalam penelitian ini yaitu petani cengkeh sebanyak 43 petani. Analisis yang digunakan yaitu analisis kualitatif deskriptif dengan memaparkan secara mendalam hal-hal yang berkaitan dengan sosial ekonomi petani cengkeh. Hasil penelitian ini yaitu: pada dimensi sosial umur petani berada pada masa produktif, pendidikan petani cengkeh berada pada pendidikan tinggi sarjana, kepemilikan pohon produktif berjumlah 25 – 199 pohon, serta kedudukan petani cengkeh adalah masyarakat biasa dengan beberapa orang petani termasuk dalam tokoh adat, tokoh agama, dan tokoh pemerintah. Dimensi ekonomi berupa pendapatan petani dari hasil produksi cengkeh, dimana pendapatan petani cengkeh berada pada nilai Rp.1.000.000 – Rp. 20.000.000 per musim panen.